Organisational Justice among Engineers at a South African Energy Provider: A Demographic Analysis - Schultz, Cecile; Molopo, Anna G.; Lessing, Karel F. (African Journal of Employee Relations, 2022)
Employees’ perceived fairness may greatly influence their employee relations, attitudes and behaviours. A demographic analysis to investigate the perceived fairness among engineers at a South African energy provider has not yet been conducted. Thus, the purpose of the current research study was to analyse the demographics of engineers at a South African energy provider in terms of organisational justice. A quantitative research method was used and 229 engineers – 164 engineers, 44 senior engineers and 21 chief engineers – participated in the study. The results showed that there were no significant relationships between the demographic variables and organisational justice. There were significant differences in how the different occupational levels perceived procedural justice, but no difference in how they perceived interpersonal justice. For the chief engineers, gender and occupational level significantly predicted organisational justice. A practical implication of the study is that the findings provided useful insight regarding the occupational level of chief engineer who perceived procedural justice in a positive light, while the occupational levels of chief engineer and engineer held a positive perception regarding organisational justice. The contribution of the study lies in the fact that all occupational levels of engineers should be treated in the same way and that demographic differences should be taken into consideration in doing so. It is recommended that management encourage a culture of employee interactions since this will improve interpersonal justice; ensure transparency regarding what is happening in the organisation; and eliminate uncertainty through employee engagement sessions.